2015
DOI: 10.4300/jgme-d-14-00710.1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Residents' Knowledge, Attitudes, Self-Efficacy, and Perceived Professional Norms Regarding Obesity, Nutrition, and Physical Activity Counseling

Abstract: Background Obesity and being overweight are both significant risk factors for multiple chronic conditions. Primary care physicians are in a position to provide health behavior counseling to the majority of US adults, yet most report insufficient training to deliver effective counseling for obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 38 publications
6
65
1
1
Order By: Relevance
“…A study24 published in 2015 has found that senior residents in primary care (Ohio, USA) had a limited knowledge of lifestyle topics and a low sense of competence in consultation on these issues. A small proportion of that study's population who participated in an elective rotation of LM training reported higher levels of LM knowledge which were accompanied by a more positive attitude towards consulting patients on these matters.…”
Section: Introductionmentioning
confidence: 99%
“…A study24 published in 2015 has found that senior residents in primary care (Ohio, USA) had a limited knowledge of lifestyle topics and a low sense of competence in consultation on these issues. A small proportion of that study's population who participated in an elective rotation of LM training reported higher levels of LM knowledge which were accompanied by a more positive attitude towards consulting patients on these matters.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research demonstrates that didactic instructional style is negatively associated with attitudes and perceived professional norms toward counseling (Antognoli et al 2016) and the rate of obesity documentation and weight loss counseling appeared unchanged following a didactic presentation (Ren et al 2016). Program directors have called for additional opportunities for residents to practice and receive feedback on counseling skills (Antognoli et al 2014, Smith et al 2015. Furthermore, evidence suggests practicing weight loss counseling with SPs improves competency and confidence in counseling, and can clinically lead to patient weight loss , Jay et al 2013, Ockene et al 1999, Burton et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies demonstrate residents lack competency in weight loss counseling, and report low self-efficacy in their counseling skills (Jay et al 2008, Hebert et al 2012, Park et al 2005, Ruser et al 2005, Vetter et al 2008, Block et al 2003, Davis et al 2008, Fluker et al 2010, Smith et al 2015. There are few published studies examining the current state of residency education on weight loss counseling, but the current evidence suggests minimal curriculum time is spent on obesity, nutrition, and physical activity counseling (Antognoli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited literature on the learning needs of medical students and trainees in this area, and what there is tends to be self-reported or elicited through survey (8,9) and lacks the richness of qualitative data that is based on experiences in practice.…”
Section: Introductionmentioning
confidence: 99%